A new proposed method of Printed Circuit Board (PCB) reverse engineering - Che Mat, Ruzinoor; Mohd Yusof, Shahrul Azmi; Zulkifli, Abdul Nasir; Daud, Ruslizam (Universiti Utara Malaysia, 2007)
One of the backbones in electronic manufacturing industry is the printed circuit board (PCB).However, with the recent rapid growth in electronics devices, the production number of the PCBs is also rapidly escalating.For electronic equipment and appliances which are based on PCB, new generations of PCB’s are being produced to suit the requirements of new products.This development can lead to waste and inefficiency when perfectly serviceable electronic components and appliances have to be scrapped because the spare PCBs are no longer available from the Original Equipment Manufacturer (OEM) or are already obsolete.This research proposes a new method for reverse engineering of an obsolete PCB.An equivalent PCB can be produce using this new methods utilizing using image processing technique.This methods involves several steps, such as Data Acquisition, PCB Scanning, Image Processing, Vectorization and CAD Editing, PCB Fabrication, and Circuitry testing and Analysis.The MATLAB Image Processing Toolbox was used in the image processing stage and AutoCAD software is used for vectorization stage.Each of these stages will be discussed in detail and newly fabricated PCB will be evaluated in terms of functionality at the end of the research.